Polyglutamine Neurodegeneration: Expanded Glutamines Enhance Native Functions - Orr, Harry T. (2012)
An intriguing set of neurodegenerative disease are the nine disorders caused by the expansion of a unstable trinucleotide CAG repeat where the repeat is located within the coding of the affected gene, i.e. the polyglutamine (polyQ) diseases. A gain-of-function mechanism for toxicity in polyQ diseases is widely thought to have a major role in pathogenesis. Yet, the specific nature of this gain-of-function is a matter of considerable discussion. The basic issue concerns whether toxicity stems from the native or normal function of the affected protein versus a novel function induced by polyQ expansion. For at least three of the polyQ disease considerable evidence is accumulating that pathology is mediated by a polyQ-induced exaggeration of a native function of the host protein.